Sense, Reference, dan Genre dalam Novel Raden Ajeng Karmiati Karya L Suma Tjoe Sing: Pendekatan Hermeneutika Paul Ricoeur - Karimah, Aisyah Akhlaqul; Dewojati, Cahyaningrum (Humanis; Vol 29 No 2 (2025), 2025)
Peranakan Chinese literature is a rich cultural heritage of the Chinese community in Indonesia. Raden Ajeng Karmiati (Satoe Romance en Drama from Pasoeroeansche Regentschappen) by L. Suma Tjoe Sing exemplifies this literary tradition, reflecting the identity and experiences of Peranakan Chinese society. This study employs qualitative methods and literature review techniques to analyze the novel's sense, referent, and genre. Using Ricoeur's hermeneutics, the research reveals the novel’s literal and referential meanings. The literal meaning aids in understanding the characters’ emotions, actions, and prevailing social norms, while the referential meaning situates the text within broader socio-cultural structures. The novel reflects Javanese social hierarchy and cultural values, enriching the interpretation of literary texts through symbolism. This study underscores the significance of Peranakan Chinese literature in capturing historical and cultural dynamics, providing insights into the interplay between literature and society.